Signal-to-noise and radiation exposure considerations in conventional and diffraction x-ray microscopy - Huang, Xiaojing (2009)
Using a signal-to-noise ratio estimation based on correlations between multiple simulated images, we compare the dose efficiency of two soft x-ray imaging systems: incoherent brightfield imaging using zone plate optics in a transmission x-ray microscope (TXM), and x-ray diffraction microscopy (XDM) where an image is reconstructed from the far-field coherent diffraction pattern. In XDM one must computationally phase weak diffraction signals; in TXM one suffers signal losses due to the finite numerical aperture and efficiency of the optics. In simulations with objects representing isolated cells such as yeast, we find that XDM has the potential for delivering equivalent resolution images using fewer photons. This can be an important advantage for studying radiation-sensitive biological and soft matter specimens.